Barbados : 2006 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
Barbados' economy continued to grow, but macroeconomic imbalances worsened. Executive Directors observed that the imbalances are owed to a procyclical fiscal stance, and advised to tighten monetary policy and safeguard the fixed exchange rate regime as an anchor of macroeconomic stability. They also emphasized to strengthen the financial sector regulatory framework and develop the financial market infrastructure. They commended the strong performance of the public pension system, banking indicators, and the agenda of CARICOM Single Market Economy (CSME).